URGENSI SUMBER DAYA MANUSIA DALAM EXPLOITASI SUMBER DAYA ALAM - -, Kasmawati (Teknosains, 2011)
Era globalization, makes technology progressively, expand for human resource need. Formal education support execution of duties which its, for that human resource in the effort how the governance and organization cooperate with other organization of goodness in also beyond the sea. Achievement something that organization beyond question not exceed other resource. Hence human resource is all important aspect which determine in state and nation likes RI. In globalization era, in line with growth and growth of life , society. SDM (human resource) remain to be studied and expressed, because basically human resource always make a move and go forward and also expand from time to time. Whereas growth of requirement to human resource which with quality mount at full speed but in useful for human being with quality as according to requirement at the present day not yet can make balance, so that happened distance which far between requirement with available human resource Keyword: human, natural-resource, exploitasi.